The Effect of Personal Characteristics of Group Members (Motivation, Participation, Women's Work Values) On the Development of Farm Women's Group - Fatonah, Siti; Hariadi, Sunarru Samsi; Santosa, Krishna Agung (JSEP (Journal of Social and Agricultural Economics), 2024)
The purpose of this research is to determine the effect of women's motivation, participation, and work value on the development of women farmer groups in Bantul Regency. This research was conducted on 27 farm women groups in 6 kapanewon in three landscapes of Bantul Regency, namely the highlands (Dlingo and Piyungan), lowlands (Kasihan and Jetis), and coastal areas (Kretek and Sanden). Landscape grouping was done by stratified random sampling, while the selection of kapanewon and farm women groups was done by simple random sampling. This research used a quantitative approach and analytical descriptive method. Total respondents were 157 people with simple random sampling technique. The data analysis method used is path analysis. The results showed that motivation has a stronger influence on the development of farm women's groups as learning classes, production units, and cooperation units than participation and the value of women's work. In addition, the value of women's work indirectly influences the development of farm women's groups with intermediate variables, namely motivation and participation.